Nonintrusive Inspection, Structures Monitoring, and Smart Systems for Homeland Security 2006
DOI: 10.1117/12.658902
|View full text |Cite
|
Sign up to set email alerts
|

Rapid-to-deploy wireless monitoring systems for static and dynamic load testing of bridges: validation on the grove street bridge

Abstract: Bridge management officials have expressed a keen interest in the use of low-cost and easy-to-install wireless sensors to record bridge responses during short-term load testing. To illustrate the suitability of wireless sensors for short-term monitoring of highway bridges, a wireless monitoring system is installed upon the Grove Street Bridge to monitor structural responses during static and dynamic load testing. Specifically, load testing of the Grove Street Bridge is conducted after its construction to valid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Examples of modern versions of these sensors are given in Figure 4 , Figure 5 and Figure 8 . The first-generation sensors continue to be extensively used in the XXI century, empowered by wireless sensing capabilities, of which developments started in the last third of the XX century (e.g., [ 52 , 53 , 54 ]) and rapidly matured in terms of commercialization and field applications (e.g., [ 32 , 55 , 56 ]). These wireless technologies are mostly based on so-called wireless nodes, which require an energy source, typically provided by a battery or an energy harvesting device.…”
Section: First Generation: Discrete Short-gauge Electrical Strain Sen...mentioning
confidence: 99%
“…Examples of modern versions of these sensors are given in Figure 4 , Figure 5 and Figure 8 . The first-generation sensors continue to be extensively used in the XXI century, empowered by wireless sensing capabilities, of which developments started in the last third of the XX century (e.g., [ 52 , 53 , 54 ]) and rapidly matured in terms of commercialization and field applications (e.g., [ 32 , 55 , 56 ]). These wireless technologies are mostly based on so-called wireless nodes, which require an energy source, typically provided by a battery or an energy harvesting device.…”
Section: First Generation: Discrete Short-gauge Electrical Strain Sen...mentioning
confidence: 99%
“…Load testing has been used to evaluate and rate bridge response, investigate fatigue life (Alampalli and Lund, 2006) and to evaluate new construction materials and technologies (Hou and Lynch, 2006;Kleinhans et al, 2007). Load testing was used to load rate a bridge in New York, USA that replaced the bridge deck with a fiber reinforced polymer (FRP) deck, that was 80% lower in weight compared to the original concrete deck (Alampalli and Kunin, 2003).…”
Section: Field Testingmentioning
confidence: 99%
“…Tasks involved in a program of load testing typically include the determination of testing objectives and load configuration, the selection and placement of instrumentation, the adoption of appropriate analysis techniques, and the evaluation and comparison of test results and analytical results [10]. Load testing is being carried out widely to evaluate and rate bridge response on a case-by-case manner to evaluate new construction materials and technologies [10,11]. While a number of bridge load testing studies can be found in the literature, such studies on bridges using embedded sensors, which is the focus of this paper, are almost nonexistent.…”
Section: Bridge Load Testingmentioning
confidence: 99%